The effects of sea water treatment on tensile and impact properties of woven sugar palm fibre reinforced unsaturated polyester composites - Ishak, Mohamad Ridzwan; Leman, Zulkiflle; Salit, Mohd Sapuan; Misri, Sairizal (2009)
The main advantages of sea water treatment compared to any other conventional treatments are low cost, their abundance of resource; cause no effect on human health and environment. This study investigates the effects of sea water treatment on the fibre surface treatment to the tensile and impact properties of woven sugar palm fibres reinforced unsaturated polyester composite. The surface properties of the sugar palm fibres were treated by soaking it in sea water for the duration of 30 days. The composite specimens of 23% weight of sea water treated fibres and untreated fibres were prepared using a compression moulding technique. The tensile and impact tests were carried out in accordance to ASTM D5083 and ASTM D256 respectively. The scanning electron microscope (SEM) reveals that the outer layer of sea water treated fibre was removed. Two-independent sample t-tests and Levene's test were employed to study the significant of the result. The results showed that the sea water treatment had significant effects on the tensile strength, tensile modulus, elongation at break and impact strength of the composites. However, it is interesting to note that the sea water treated composites had statistically significant decrease in all of these properties. In conclusion, even though the sea water treatment removed the outer layer of fibre but the treatment did not improve the tensile and impact properties of the composites.